ANALISIS KINERJA PEGAWAI BERDASARKAN DISIPLIN KERJA, MOTIVASI, KOMPENSASI DAN GAYA KEPEMIMPINAN PADA RUMAH SAKIT UMUM DAERAH DATU BERU TAKENGON - Win, admin; Azhari (LPPM-UNIKI, 2022)
The purpose of this study is to prove and analyze the Influence of work discipline, work motivation, compensation and leadership style on the performance of the employees of RSUD Datu Beru Takengon. The study was conducted on a sample of 213 employees with data collection through questionnaires and data analysis with a quantitative approach based on path analysis. The results showed that; a) there is a significant positive effect of employee discipline on their performance of 9.14%, b) there is a positive influence of work motivation on employee performance of 8.75%, c) there is a positive influence of compensation factors on employee performance that is 9.10 %, and d) there is a significant effect of leadership style variable on employee performance by 8.45%, and e) there is a simultaneous effect of work discipline, work motivation, compensation and leadership style on employee performance at Datu Beru Takengon Central Aceh Hospital of 35.7 %.